VISCERAL LEISHMANIASIS IN HAZARA - Zaman, Sharif -uz-; Wazir, Mehr Dil Khan; Khaliq, M.A.; Ahmad, Shakeel; Shah, Waheed (Journal of Ayub Medical College Abbottabad, 1989)
Abstract: Seven cases of visceral leishmaniasis are reported. They were seen during 1988 and were between the ages of 1-1/2-8. One patient left without treatment, another left while the treatment was just started. One died before treatment could be started due to late availability of the drug. Four remaining patients were treated with pentavalent antimony compounds, blood transfusion and general supportive treatment. Two out of four patients were treated successfully while the other two are under treatment and improving.